Implementation of the Teams Games Tournament (TGT) Learning Model Assisted with Lost Card Media to Improve the Numeration Abilities of Class I Students in Primary Schools - Rara Deyu Kaslita; Yantoro Yantoro; Violita Zahyuni; Risti Risti Meylani (Jurnal Tonggak Pendidikan Dasar : Jurnal Kajian Teori dan Hasil Pendidikan Dasar, 2023)
This research aims to describe the application of the Teams Games Tournament (TGT) learning model assisted by Missing Card media to improve the numeracy skills of Class I students in elementary schools. The subjects of this research were 24 grade 1 students at SD Negeri 078/I Teluk Ketapang. This research is classroom action research (PTK). Observation, interviews, tests, and documentation were obtained from this research data. The results of research that implemented the Teams Games Tournament learning model assisted by Lost Card media showed an increase in students' numeracy skills as indicated by recapitulation data which was guided by indicators of class I students' numeracy abilities. The percentage of students' numeracy abilities in cycle II reached 79.16%. there was an increase in numeracy ability, which in the pre-cycle was 29.16%. and cycle I reached 59.09%.